(untitled) (Revista Apotheke, 2021)
In this text I present a brief overview of the works of the artist Hariel Revignet (Gabão / Goiás, 1996) in dialogue with concepts both used by the artist. I am interested in approaching his production in relation to the contemporary context in which the production of black and black artists is found, in the present Afro-Brazilian Art. Reflecting on a socially engaged practice in which the artist builds a collective practice between experiences with black and indigenous women, as an essential factor to her existence and narratives of herself linked to the research and creation process.